Heterogeneous Cu/OMS-2 as an efficient catalyst for the synthesis of tetrasubstituted 1, 4-enediones and 4H-pyrido[1, 2-a]-pyrimidin-4-ones. Issue 106 (14th October 2015) - Zhang, Jinqi; Meng, Xu; Yu, Chaoying; Chen, Gexin; Zhao, Peiqing
Abstract : Copper supported on OMS-2: a heterogeneous catalyst Cu/OMS-2 was prepared for the synthesis of tetrasubstituted 1, 4-enediones and 4 H -pyrido[1, 2- a ]-pyrimidin-4-ones under the same conditions with air as the oxidant. Abstract : An efficient Cu/OMS-2-catalyzed oxidative heterogeneous protocol has been developed for the synthesis of tetrasubstituted unsymmetrical 1, 4-enediones and 4 H -pyrido[1, 2- a ]-pyrimidin-4-ones from 1, 4-enediones and amines or 2-aminopyridines. The present catalytic system employs air as the terminal oxidant and tolerates a broad range of substrates using low loading copper (1.3 wt%). The Cu/OMS-2 was characterized by various methods, including XRD, XPS, BET as well as TEM/SEM, and the results of H2 -TPR shows that the redox ability of the catalyst was improved by the combination of Cu and OMS-2. Moreover, the catalyst is recyclable.